2018
DOI: 10.2298/gensr1802519g
|View full text |Cite
|
Sign up to set email alerts
|

Molecular taxonomy and phylogenetics of Daedaleopsis confragosa (Bolt.: Fr.) J. Schröt. From wild cherry in Serbia

Abstract: Daedaleopsis spp., a lignicolous fungus causes of white rot on wild cherry and other broadleaved species and makes economic losses in Serbian forestry. The paper presents results of two morphologically distinct fungi Daedaleopsis confragosa and Daedaleopsis tricolor isolated from native populations of wild cherry (Prunus avium L.) found in the sites of Protected Forests of Serbia. Morphological appearance of D. tricolor was found more abundant in comparison to D. confragosa species. Samples from Serbia were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Traditionally, morphological characteristics have been used by expert taxonomists, systematic biologists and trained practitioners to identify species after earning substantial experience in the field (EFTEKHARIAN et al, 2018); KRESS and ERICKSON, 2008). As the significance of biodiversity is increasing day by day in the field of agriculture, evolutionary biology, ecology, conservation biology and other fields, therefore correct identification of plant taxa is very necessary, while DNA barcode is an important tool for the modern-day plant identification and delimitation (BAYAT et al, 2018;GALOVIĆ et al, 2018;WANG et al, 2018). Recent advances in the field of genomics and bioinformatics are incomplete without the use of DNA sequences (SEVĠNDĠK and YALÇIN, 2018;SAVIĆ et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, morphological characteristics have been used by expert taxonomists, systematic biologists and trained practitioners to identify species after earning substantial experience in the field (EFTEKHARIAN et al, 2018); KRESS and ERICKSON, 2008). As the significance of biodiversity is increasing day by day in the field of agriculture, evolutionary biology, ecology, conservation biology and other fields, therefore correct identification of plant taxa is very necessary, while DNA barcode is an important tool for the modern-day plant identification and delimitation (BAYAT et al, 2018;GALOVIĆ et al, 2018;WANG et al, 2018). Recent advances in the field of genomics and bioinformatics are incomplete without the use of DNA sequences (SEVĠNDĠK and YALÇIN, 2018;SAVIĆ et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Our study suggests that pollen features, that is, the size and shape of the reticula, colpus ornamentation exhibit a continuous range of variation within the genera and could be a useful tool to differentiate Lamioideae taxa (Xiang, Funamoto, Evangelista, Zhang, & Peng, 2013). Moreover, Lamioideae taxa should be further screened out for its foliar epidermal studies through following the previous methods (Vastag et al, 2019), phytochemical (Ivanišević et al, 2019) and molecular studies (Galović et al, 2018; Sheidai, Koohdar, & Poode, 2018). Our present finding showed that the pollen morphology of the study taxa showed some overlap taxonomic characters and some important characters to differentiate the study taxa.…”
Section: Resultsmentioning
confidence: 99%